Current research opportunities for potential phytotherapeutic agents for the treatment of pathologies of the female reproductive system - Sokolik, Olena Petrivna; Prozorova, Galina Olexandrivna (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Herbal medicine is prescribed for various disorders of the menstrual cycle (uterine bleeding, dysmenorrhea), for the treatment of premenstrual and climacteric syndromes, inflammatory diseases of the genital organs, mastopathy and mastalgia and other pathological conditions. The aim of the study is to analysis and generalization of data from professional literature and own experience in the treatment of patients with pathologies of the female reproductive system by phytotherapeutic methods, taking into account the influence of medicinal plants on various links in the pathogenesis of the disease, as well as making recommendations for improvement and prospects for the use of phytotherapy in the treatment of this pathology. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. To make an analysis of literary sources of domestic and foreign authors about usage of medicinal plants for the treatment of pathologies of the female reproductive system. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of the literature. In the treatment of primary (spasmodic) dysmenorrhea, herbal remedies with an antispasmodic, analgesic, hormone-mimetic effects are prescribed. It can be Chamomile (Matricaria chamomilla L.), Achillea millefolium, commonly known as yarrow, Viburnum, Shepherd’s purse (Capsella bursa-pastoris), Greater celandine, Atropa belladonna, Hyoscyamus niger, commonly known as henbane, black henbane, or stinking nightshade and Abraham’s tree. Many plants have bactericidal activity, and this property is used in the treatment of inflammatory diseases of the mucous membranes and skin. Such properties are possessed by flowers of Chamomile (Matricaria chamomilla L.), Calendula officinalis, infusion of Medicinal sage (Salvia officinalis L.). For the treatment of functional hyperprolactinemia phytopreparations are also successfully used. It is known that the medicinal plant Vitex agnus castus has dopaminergic properties, selectively blocking prolactin synthesis, and reduces follicle stimulating hormone levels. Strychnos ignatia, Caulophyllum thalictroides, European cyclamen, Lilium tigrinum, Iris versicolor provide a complex effect on the female body, effectively reduces the level of prolactin and the severity of mastalgia, which is confirmed not only by clinical data, but also by mammography data in fibrocystic breast disease. For the treatment of climacteric syndrome, a large number of medicinal plants are used, in particular, the most popular is the Cimicifuga racemose. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The effectiveness of phytotherapeutic drugs has been verified by many clinical trials. Modern phytotherapy is becoming more widespread in clinical practice, as an alternative to drug treatment.